La convertibilidad en Argentina: Funcionamiento de una caja de conversión anclada al dólar - Canavese, Alfredo (2020)
This paper establish the conditions that originate the Currency Boards in Argentina and shows the macroeconomics performance of that country since the beginning of Convertibility to 1998. He determines the eftects of the tequila, Russian and Brazilian crises over convertibility. Distinguishes clearly ditterences between “doliarization” and currency boards and conciudes that the success of convertibility was based on structural reforms and inflow of capitals. Nevertheless, the currency boards is very hard to manage when a great mount of capitals run out the country.